Penanggulangan Timbulan Sampah di Perumahan Bukit Mekar Wangi Menggunakan Bangunan TPS 3R - Lutfi, Muhamad; Chayati, Nurul; Alimuddin, Alimuddin; Sidik, Sendi Abduloh; Insan, Muhammad Khaerul; Syaja'ah, Siti Kholifah (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2025)
The problem of waste generation in urban areas continues to increase along with population growth. An increase in population of 0.98% in the research location contributed to the high volume of waste. This research aims to get a design, especially in the layout, structural analysis of the 3R Waste Temporary Shelter (TPS) building and cost budget plan (RAB). In the process of building a TPS 3R building, several technical aspects are considered in order to determine the layout of the building and the strength of the building construction so that it can function optimally. The method used uses structural analysis calculations, while checking beams and columns using ETABS ver.21 software. Based on the structural analysis, the TPS 3R building is planned with dimensions of 19.3 × 4.2 m using reinforced concrete material with a roof covering structure in the form of a concrete deck. The structural material specifications used are concrete with a quality of 22.84 MPa and the yield quality of reinforcing steel (fy) 420 MPa. The dimensions of the column structural elements are K30x30 cm, B20x40 cm main beam and 12 cm thick concrete slab. The structural analysis output of the planned building shows purple-colored columns with a strength ratio of 0.90 to 0.95, indicating that the structure is reasonably safe against working loads. Meanwhile, the black-colored beams indicate that the structure is safe against the working load. Keywords: Waste generation, TPS 3R, Structural analysis.